Power Relations and Resistance in Naguib Mahfouz’s Layali Alf Laylah: Michel Foucault's Hegemony - Alandira, Palendika; Rohanda, Rohanda; Taufiq, Wildan; Firdaus, Rifqi Muhammad (Jurnal Adabiyah, 2025)
This research examines the relationship between power and resistance in Layali Alf Laylah, a novel by Najib Mahfouz, through the lens of Foucault's hegemony theory. This qualitative research employs an analytical descriptive approach. The material object analyzed is the novel Layali Alf Laylah, while the formal object is Foucault's hegemony theory, which explores the influence of power on individuals and the emergence of resistance against established power structures. The analytical descriptive method is utilized to examine the text and to identify the various forms of power and resistance mechanisms embedded within the characters and narrative of the novel. The findings indicate that the novel portrays repressive power dynamics while simultaneously presenting resistance against these power structures through both individual and collective actions. Consequently, the novel not only illustrates the existing power relations but also highlights how resistance plays a crucial role in the process of social change. In conclusion, Layali Alf Laylah offers a nuanced depiction of the interplay between power and resistance within a society shaped by dominant power structures. The novel provides critical insight into the complexities of hegemonic influence and the potential for subversion, reinforcing the dynamic nature of societal power relations. This research contributes to the body of knowledge by providing a deeper understanding of the dynamics of power and resistance in literature, demonstrating how Foucault’s theoretical framework can be applied to analyze social structures within fictional narrative. ملخص يهدف هذا البحث إلى تحليل علاقة السلطة والمقاومة في رواية "ليالي ألف ليلة" لنجيب محفوظ باستخدام نظرية الهيمنة لفوكو. يعتمد هذا البحث على المنهج النوعي مع مقاربة وصفية تحليلية. الموضوع المادي الذي يتم تحليله هو رواية "ليالي ألف ليلة"، بينما الموضوع الشكلي هو نظرية الهيمنة لفوكو، مع التركيز على تأثير السلطة على الأفراد وكيفية ظهور المقاومة تجاه الهياكل السلطوية القائمة. يتم استخدام المنهج الوصفي التحليلي لاستكشاف النص وتحديد أشكال السلطة وآليات المقاومة التي تتجلى في الشخصيات وحبكة الرواية. تظهر نتائج البحث أن الرواية تصور ديناميات السلطة التي تتسم بالقمع، لكنها تقدم أيضًا مقاومة للهياكل السلطوية من خلال أفعال الأفراد والجماعات. وبذلك، فإن الرواية لا تكتفي بكشف العلاقات السلطوية القائمة، بل توضح كيف تصبح المقاومة جزءًا من عملية التغيير الاجتماعي. وفي الختام، تُظهر رواية "ليالي ألف ليلة" تمثيلًا معقدًا لتفاعل السلطة والمقاومة في مجتمع يتأثر بهياكل السلطة. Abstrak Penelitian ini bertujuan untuk menganalisis relasi kuasa dan resistensi dalam Novel Layali Alf Laylah karya Najib Mahfouz dengan menggunakan teori hegemoni Foucault. Jenis penelitian ini adalah kualitatif dengan pendekatan deskriptif analitis. Objek material yang dianalisis adalah Novel Layali Alf Laylah, sedangkan objek formalnya adalah teori hegemoni Foucault, yang berfokus pada pengaruh kuasa terhadap individu dan bagaimana resistensi muncul terhadap struktur kekuasaan yang ada. Metode deskriptif analitis digunakan untuk menggali teks dan mengidentifikasi bentuk-bentuk kuasa serta mekanisme resistensi yang terjalin dalam karakter-karakter dan alur cerita novel. Hasil penelitian menunjukkan bahwa novel ini menggambarkan dinamika kuasa yang bersifat repressif, namun juga menyajikan perlawanan terhadap struktur kuasa tersebut melalui aksi-aksi individu dan kelompok. Dengan demikian, novel ini tidak hanya mengungkapkan hubungan kuasa yang ada, tetapi juga memperlihatkan bagaimana resistensi menjadi bagian dari proses perubahan sosial. Kesimpulannya, Layali Alf Laylah menyajikan representasi kompleks mengenai interaksi kuasa dan resistensi dalam masyarakat yang dipengaruhi oleh struktur kekuasaan.